Graphics for urban design. - Meeda, Bally (ICE Publishing, 2018)
This is a guide to producing high quality illustrations in urban design projects and plans. The authors describe high quality material as being clear, relevant, accessible, honest and attractive. Topics covered include context, participation, analysis, outputs, and good practice.